A historical perspective on the life cycle of a tourist activity: dolphin watching in Brazil’s Fernando de Noronha archipelago - Tischer, Marina Consuli; Schiavetti, Alexandre; Silva, Flávio José de Lima; Silva-Jr, José Martins da (Ethnobiology and Conservation, 2018)
In Brazil, the whale watching is practiced with different species, such as whales, dolphins, and porpoises. This activity facilitates the growth of the economic activities of communities in many regions of the country, and it may be a tool for awareness about the marine preservation and conservation. Moreover, the whale watching also impacts native species. Fernando de Noronha (FN) is a worldwide watching tourism site due to the time of the development of watching activities in the region and the ease to watch cetaceans, mainly the spinner dolphin (Stenella longirostris). The history of dolphin watching tourism in FN was developed concomitantly with the tourism destination of the archipelago as a whole. The aim of this study was to characterize the dolphin watching in FN by considering the development, supply and demand, laws and future perspectives of the region. We also aim to identify the main events or stages that promoted a more significant change throughout the history of the activity in the archipelago. Additionally, we will investigate the applicability of the “Tourism Area Life Cycle” (TALC) approach for a tourism activity. We observed that both land-based and boat-based (boat trips) are available in FN. The boat trips are more common and involve the triple of tourists than land-based watching. However, the last provides more informative and educational component. Through TALC analysis, dolphin watching in FN had its development together with the destination development and, currently, both areas present stagnation stage indicators. In addition, the land-based watching, for being less impacting and more educative, has potential to increase the visitation.